Calculation and Interpretation of Fractional Green Canopy Cover in the Southwest of Buenos Aires through an Open-Source Mobile Application - Jouglard, Juan (2021)
Within the province of Buenos Aires, there is a region known as the semi-arid southwest, integrated by Bahia Blanca, Coronel Rosales, Tornquist, Puan, and Coronel Pringles. In this area, it is possible to find not only bare soil but also soils with dry or alive plant material. It is in the interest of both INTA and the landowners in this area to study soil cover to achieve better decision-making on environmental and productive impact and take advantage of resources in the most efficient way possible. For example, bare soil runs great risks of wind and water erosion. Through proper analysis and estimation, these problems could be prevented. Our proposal is a mobile application, open-source and freely available, that that speeds up the coverage calculation, supports data interpretation and decision-making regarding the coverage and management of soils through photographs taken from mobile devices and synchronized with the cloud. Unlike other existing solutions, our development distinguishes between bare soil, soils covered with alive plant material, and soil covered with dry plant material.